1990
DOI: 10.1159/000132885
|View full text |Cite
|
Sign up to set email alerts
|

Common fragile sites in man and three closely related primate species

Abstract: The expression of common fragile sites was studied in peripheral lymphocytes of man, gorilla, chimpanzee, and orangutan after induction with aphidicolin, methotrexate, or fluorodeoxyuridine. As far as the chromosomal localization is concerned, it appears that many of these sites have been highly conserved during primate evolution. However, differences were found in the relative expression of certain sites. In all four species, mapping of approximately 500 lesions disclosed the most breakage-prone common fragil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…In addition to the conservation of CFS expression levels among different mouse strains, we found the same for syntenic regions of the mouse and human genomes. Such conservation was already described for the most frequent human CFSs compared to the genomes of different great apes (Yunis and Soreng 1984;Smeets and van de Klundert 1990). Our data shown in Figure 5 support the conclusion that a conservation is also true for less frequent CFSs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition to the conservation of CFS expression levels among different mouse strains, we found the same for syntenic regions of the mouse and human genomes. Such conservation was already described for the most frequent human CFSs compared to the genomes of different great apes (Yunis and Soreng 1984;Smeets and van de Klundert 1990). Our data shown in Figure 5 support the conclusion that a conservation is also true for less frequent CFSs.…”
Section: Discussionsupporting
confidence: 88%
“…Cytogenetic CFS mapping studies on murine lymphocytes revealed 19 CFSs defined as chromosome bands with significantly elevated gap/break frequencies that expressed the lesion homozygously as well (Elder and Robinson 1989). Comparative analysis in lymphocyte chromosomes of human, three great apes (chimpanzee, gorilla, orangutan), and a simian monkey species (Macaca fascicularis) has demonstrated that a high percentage of human CFSs were found in the equivalent location on chromosomes of apes/monkeys, although with sometimes significantly different expression frequencies (Yunis and Soreng 1984;Smeets and van de Klundert 1990;Ruiz-Herrera et al 2002). A possible coincidence of CFSs with evolutionarily rearranged sites was also described (Smeets and van de Klundert 1990;RuizHerrera et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fragile sites have been reported in mouse, rat, hamster, cow, cat, and dog (35)(36)(37)(38)(39)(40). They appear to be inherent and universal structures of the mammalian genome.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from human beings, the FS have been found in other animal species. The gorilla and the chimpanzee are some examples of species evolutionally close to the man, where have been found (Yunis and Soreng 1984, Schmid et al 1985, Smeets and Klundert 1990. The mole rat Nesokia indica (Tewari et al 1987), the Persian vole Ellobius lutescens (Djalali et al 1985), the Chinese hamster (Simi et al 1989) and Drosophyla melanogaster (Laird et a!.…”
mentioning
confidence: 99%